Efficiency of Ethiopian commercial banks: using data envelopment analysis. (30th September 2020) - Ijara, Tafa Mosisa; Sharma, Dhiraj
This study investigates the overall technical, pure technical and scale efficiencies of Ethiopian commercial banks from 2014 to 2018 using data envelopment analysis (DEA). The intermediation approach applied to select variables, both CCR (Charnes, Cooper and Rhodes) model and BCC (Banker, Charnes and Cooper) model used to identify the main causes of inefficiency. The study found that only two banks were consistently efficient in all measurements types and the average of overall technical, pure technical and scale efficiencies reveals that Ethiopian commercial banks were inefficient during the period. This result would have negative implications on Ethiopian economy. Moreover, their inefficiency was caused mostly by management related problems than scale related factors. Therefore, the bank managers are suggested to take appropriate action based on their respective causes of inefficiency and National Bank of Ethiopia and other regulatory bodies should enforce the policy to enhance the overall efficiency of the sector.